Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1600-6143.2004.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pharmacogenetics on the Time to Achieve Target Tacrolimus Concentrations after Kidney Transplantation

Abstract: Previously, we reported that, at 3 months after renal transplantation, individuals with CYP3AP1 genotype CYP3AP1 * 1 (linked to CYP3A5 * 1 and strongly associated with expression of CYP3A5) required twofold higher doses of tacrolimus to achieve target blood concentrations than individuals with the genotype CYP3AP1 * 3/ * 3 (CYP3A5 nonexpressors). This study assesses the relationship between concentrationcontrolled dosing during the early period after transplantation, the time to achieve target concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
169
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(182 citation statements)
references
References 29 publications
12
169
0
1
Order By: Relevance
“…Previous studies have found that gene polymorphisms, particularly in CYP3A5, affect tacrolimus concentration-dose relationships, so predicting initial dose requirements in lung transplant recipients (32)(33)(34). In kidney transplant recipients, a polymorphism of CYP3A5 was found to be a risk factor for acute rejection and nephrotoxicity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that gene polymorphisms, particularly in CYP3A5, affect tacrolimus concentration-dose relationships, so predicting initial dose requirements in lung transplant recipients (32)(33)(34). In kidney transplant recipients, a polymorphism of CYP3A5 was found to be a risk factor for acute rejection and nephrotoxicity (35).…”
Section: Discussionmentioning
confidence: 99%
“…17 Kidney transplant recipients with the CYP3AP1*1 genotype require up to twofold higher doses of tacrolimus to achieve comparable blood levels at 3 months after transplantation compared with patients with the CYP3AP1*3/*3 genotype. 18 SNPs can be associated with functional differences of proteins or diseases even if they are intronal and are not transcribed. One of the most established examples for such an effect is the significant association of the intronic rs708487 polymorphism in the prostanoid DP receptor gene with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who carry one or more CYP3A5*1 alleles express the CYP3A5 enzyme [28,29]. Tacrolimus is a substrate for CYP3A5 and it is well established that individuals carrying one or more *1 alleles have a higher tacrolimus CL and lower trough concentrations [11][12][13][14]17]. Several previous studies have highlighted the differences in CL/F and dose requirements for the CYP3A5*1 carriers compared with individuals with the CYP3A5*3/*3 genotype [24,[30][31][32][33][34].…”
Section: Figurementioning
confidence: 99%
“…In an earlier study on the pharmacokinetics of tacrolimus in healthy Japanese subjects,CL/F was about 1.5 times higher in the CYP3A5*1 carriers (*1/*1 or *3/*3 genotype) as compared with the CYP3A5*3/*3 genotype [35]. Most studies have combined genotype groups (*1/*1 with *1/*3) due to sample size limitations [13][14][15]36]. Given our large sample size, we were able to define the differences in tacrolimus CL/F between three CYP3A5 genotype groups.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation